Religions and low fertility today - Rašević Mirjana (Stanovništvo, 2019)
Our understanding of whether, to what extent, and under which conditions religions nowadays influence birth levels depends on research. It is important to seek answers to two fundamental questions. The first question is about the role of religiosity and religious affiliation in the deterministic cause of low fertility and family planning in recent times. The second question deals with the influence of religious institutions on birth levels and the exercise of reproductive rights at the global level and within certain population groups over recent decades. To that end, the paper provides an overview of theoretical examinations of the connection between religions and fertility, empirical studies addressing low completed fertility, birth control, or sexual behaviour in relation to religiosity or religious affiliation of individuals, as well as the influence of religious institutions on fertility transition and the respect of human rights in this field. A review of the recent studies of various populations characterised by low birth levels shows that religiosity, especially practising religion, encourages people to uphold traditional values, attitudes, and behaviours that are directly or indirectly related to the concepts of marriage and childbearing. Moreover, it sheds light on some examples of religious institutions’ concrete opposition to progress in this area, while also highlighting contradictory cases of religions supporting pro-found contemporary changes in reproductive behaviour. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. III 47006]